Hemisection and porcelain fused to metal crown splinters on the first molar: A case report - Yunita Styaningrum; Rebbecca A. Kuncoro; Raphael TE. Untara; Yulita Kristanti (Journal of Dentomaxillofacial Science, 2022)
Objective: The aim of this treatment was to preserve the remaining tooth structure and to restore the function of the tooth Methods: A 37-year-old female patient with a chief complaint of pain in the lower right molar tooth after root canal treated one week ago. Clinical examination revealed a cavity on the disto-occlusal side achieve half the crown of the tooth with a dentin depth. Percussion: (+), palpation: (-), mobility: (-), vitality: (-). Radiograph examination revealed radiolucent area mesial root and ± 1.5mm radiopaque images that are thought to be file fractures in the apical foramen. Vertical radiolucent lines on dental bifurcation were detected vertical bone loss was evident on mesial root of the lower right molar with furcation involvement. Management of the patient is hemi section and Porcelain fused to metal crown splinter. Results: After one month of hemi section, no pain detected, the gingiva shows good healing, no Intra and extraoral swelling, trismus was absent, and objective examination percussion test was (-) and mobility (-). Conclusion: Hemi section is a conservative and effective treatment of choice overcome vertical radiolucent lines on dental bifurcation and broken file in the apical foramen.